2014
DOI: 10.1177/1358863x14529617
|View full text |Cite
|
Sign up to set email alerts
|

Use of fractional flow reserve in the assessment of chronic mesenteric ischemia

Abstract: Chronic mesenteric ischemia (CMI) is a rare condition that is usually the result of atherosclerotic obstructive disease affecting the mesenteric arteries. The classic triad of post-prandial pain, food aversion and weight loss is not always present, often leading to low clinical suspicion for CMI and underdiagnosis. Non-invasive evaluation for CMI usually starts with mesenteric arterial duplex scanning, followed by computed tomography angiography, magnetic resonance angiography or conventional angiography, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Sadiq et al reported on a 67-year-old male, presented with acute myocardial infarction, requiring emergent coronary artery bypass graft (CABG) surgery due to severe multi-vessel coronary artery disease [16]. Due to disabling symptoms secondary to severe obstructive disease of the distal abdominal aorta and bilateral common iliac arteries, the patient underwent a peripheral intervention.…”
Section: Reviewmentioning
confidence: 99%
“…Sadiq et al reported on a 67-year-old male, presented with acute myocardial infarction, requiring emergent coronary artery bypass graft (CABG) surgery due to severe multi-vessel coronary artery disease [16]. Due to disabling symptoms secondary to severe obstructive disease of the distal abdominal aorta and bilateral common iliac arteries, the patient underwent a peripheral intervention.…”
Section: Reviewmentioning
confidence: 99%
“…There are just a few case reports for the probable significance of FFR in mesenteric disease [ 84 ]. The splanchnic circulation and its response to vasodilating stimuli is poorly understood and understudied.…”
Section: Functional Assessment Of Intermediate Mesenteric Stenosismentioning
confidence: 99%
“…Sadiq et al . [ 1 ] applied the FFR measurement in a CMI case, and demonstrated that the baseline resting pressure gradient of stenosis in SMA was 14 mmHg (FFR = 0.87), hyperemic pressure gradient was 37 mmHg (FFR = 0.65). After stenting, the FFR results became 0.95 and 0.85, which suggested a significant improvement postintervention.…”
Section: F Ractional F Low R mentioning
confidence: 99%
“…Second, unlike the brief and transient changes in renal vasomotor tone, the flow is dynamic with routine postprandial hyperemia in the mesenteric arterial bed. [ 1 ] Thus, it is crucial to induce hyperemic condition in measuring a FFR in the mesenteric arteries, particularly in SMA, as hyperemic flow mimics the routine postprandial flow. Last but not least, the circulatory control of splanchnic perfusion is still poorly understood, so is the response to pharmacologic induced hyperemia in mesenteric arteries.…”
Section: F Ractional F Low R mentioning
confidence: 99%
See 1 more Smart Citation